An exploratory meta-analytic review on the empirical evidence of differential learning as an enhanced motor learning method - Tassignon, B.; Verschueren, J.; Baeyens, J.-P.; Benjaminse, A.; Gokeler, A.; Serrien, B.; Clijsen, R. (Frontiers in Psychology, 2021)
Background: Differential learning (DL) is a motor learning method characterized by high amounts of variability during practice and is claimed to provide the learner with a higher learning rate than other methods. However, some controversy surrounds DL theory, and to date, no overview exists that compares the effects of DL to other motor learning methods.